2012
DOI: 10.5695/jkise.2012.45.5.198
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Characteristics of the Sulfuric Acid Anodized Film Formed on Al6070 Alloy in Nitric Acid Vapor Environment

Abstract: The corrosion properties of anodized films on aluminium 6070 alloy in a sulfuric acid have been studied. Comparison to evaluate the anodized A6070 and pure 6070 specimen, corrosion tests in HNO 3 vapor environment of the 20 wt.% were performed up to 72 hours. Characteristics of film formation and surface morphology were examined by optical microscopy, FE-SEM, and EDS. The oxide film anodized in the sulfuric acid solution contained 5 to 10 wt.% of sulfur. In the initial stages of corrosion, anodized specimens e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Sulfuric acid (H 2 SO 4 ) electrolytes are often used in industries because of their economical advantage, and many studies have reported optimal conditions using sulfuric acid anodized coatings [2][3][4][5]. However, when sulfuric acid electrolytes are used, sulfuric acid ions remain in the oxide film, creating a film with low purity that is more susceptible to corrosion [6]. For this reason, anodizing processes using organic acids have been actively researched.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfuric acid (H 2 SO 4 ) electrolytes are often used in industries because of their economical advantage, and many studies have reported optimal conditions using sulfuric acid anodized coatings [2][3][4][5]. However, when sulfuric acid electrolytes are used, sulfuric acid ions remain in the oxide film, creating a film with low purity that is more susceptible to corrosion [6]. For this reason, anodizing processes using organic acids have been actively researched.…”
Section: Introductionmentioning
confidence: 99%